Tuning brain networks: The emerging role of transcranial direct current stimulation on structural plasticity - Barbati, Saviana Antonella; Podda, Maria Vittoria; Grassi, Claudio (Frontiers in Cellular Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that has been proven to promote beneficial effects in a range of neurological and psychiatric disorders. Unfortunately, although has been widely investigated, the mechanism comprehension around tDCS effects presents still some gaps. Therefore, scientists are still trying to uncover the cellular and molecular mechanisms behind its positive effects to permit a more suitable application. Experimental models have provided converging evidence that tDCS elicits improvements on learning and memory by modulating both excitability and synaptic plasticity in neurons. More recently, among tDCS neurobiological effects, neural synchronization and dendritic structural changes have been reported in physiological and pathological conditions, suggesting possible effects at neuronal circuit level. In this review, we bring in focus the emerging effects of tDCS on structural plasticity changes and neuronal rewiring, with the intent to match these two aspects with the underpinning molecular mechanisms identified so far, providing new perspective to work on to unveil novel tDCS therapeutic use to treat brain disfunctions.